The Role Of Experiential Marketing In The Development Of Minangkabau Cultural Tourist Destinations In Sijunjung Traditional Villages - Evanita, Susi; Asri, Zul; Indrayuda, Indrayuda; Fahmi, Zul; Syofyan, Rita (Institute for Law and Economics Studies, 2025)
The tourism industry has now become an important icon to introduce a region to domestic and international tourists. The growth of tourism provides an opportunity to have a positive impact on local communities, leading to economic development and improved welfare, especially around tourist destinations. The Sijunjung Traditional Village tourist destination, which is a cultural landmark of West Sumatra, features unique customs, culture and village landscapes that resemble traditional Minangkabau villages. The village's traditional houses, such as the Rumah Gadang, demonstrate a fusion of cultural elements while promoting cultural harmony. This area is part of the Ranah Minang Silokek Geopark development project which aims to preserve, restore and enhance the tourism sector to improve the local economy. This service is conducted through the Nagari Binaan (PPNB) development program of Padang State University through development initiatives such as training programs and mentoring sessions. These efforts are made to empower local communities, managers, creative economic actors, and cooperative management and members through local wisdom and cultural values to create an attractive cultural experience for tourists, encourage economic growth, and preserve cultural heritage.